The Pengaruh Lingkungan Kerja, Kepuasan Kerja Dan Disiplin Kerja Terhadap Kinerja Karyawan Bank BNI (Persero) Tbk Cabang Jababeka Kabupaten Bekasi - Shary Limbong; Solehudin Solehudin; Didit Supriyadi (Journal of Economic, Bussines and Accounting (COSTING), 2022)
The decline in employee performance in implementing the new work system carried out by Bank BNI Jababeka Cikarang Branch during the Covid-19 pandemic was allegedly caused by several factors such as the work environment, job satisfaction and work discipline. Therefore, the purpose of this study is to examine the effect of work environment, job satisfaction and work discipline on employee performance at PT. Bank BNI (Persero) Tbk Jababeka Cikarang Branch. The research method used is quantitative with the data analysis used is descriptive statistics and verification. While the data analysis unit used path analysis. The population in this study were all employees of Bank BNI (Persero) Tbk Jababeka Cikarang Branch with a total of 253 people with a sample of 155 people where the sampling technique used was simple random sampling. The results showed that the work environment, job satisfaction and work discipline partially positive and significant effect on the performance of employees of PT. Bank BNI (Persero), Tbk Jababeka Cikarang Branch. Simultaneously shows that the work environment, job satisfaction and work discipline have a positive and significant effect on the performance of employees of PT. Bank BNI (Persero), Tbk Jababeka Cikarang Branch. Keywords: work environment, job satisfaction, work discipline, performance.